Implementation of the Common Core State Standards Recommendations for the Department of Defense Education Activity Schools - Saavedra, Anna Rosefsky (RAND Corporation, 2012)
The Department of Defense Education Activity (DoDEA) recently adopted the Common Core State Standards (CCSS). This paper draws on prior literature on the implementation of large-scale educational reforms to frame CCSS implementation in terms of eight core tasks, each tailored to the DoDEA context. These tasks are based on a synthesis of scale-up efforts from 15 diverse, large-scale reforms.